Application Of Home Visit Recording And Reporting Systems For Vulnerable Family For Health Nurses In Indramayu Regency Public Health Centre - Yulianingsih, Nengsih; Priyanto, Priyanto; Nurohmat, Nurohmat (Universitas Pendidikan Indonesia, 2021)
The partner's problem discussed in the program community service is about less than the maximum recording and reporting of home visit activities for vulnerable families in the area of the Indramayu district health center area.. The problems that always happen are that there is No. enough time that causes no recording and report system effectiveness. In addition, there are not enough human resources. The rapid rotation and shifting of nurses' duties so that nurses' comprehension of health facilities has not been maximized cause an impact on attainment of the target of home visits for vulnerable families under the predetermined target.